What really happened in The Hague? - Barbara Buchner (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper investigates the occurrences at the Sixth Conference of the Parties to the 1992 United Nations Framework Convention on Climate Change (UNFCCC) which took place in The Hague, The Netherlands, from the 13th to 25th November of 2000. Since the conference did not reach an agreement there exists a broad interest in knowing what really happened during the negotiations. The aim of the analysis is to give greater insight to reasons of the climate talks' failure and to progress made during the negotiations. Following the discussions of the issues surrounding the talks in The Hague, the paper will also look forward as to possible solutions and ideas for an eventual agreement.
Keywords: E61; F18; H4; H77; O38; Q01; Q38; Q48; 330; Climate change; Kyoto Protocol; international political process; Klimaschutz; Internationale Umweltpolitik; Verhandlungen; Welt